If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = 2x + 30 Reorder the terms: 12 + 4x = 2x + 30 Reorder the terms: 12 + 4x = 30 + 2x Solving 12 + 4x = 30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 4x + -2x = 30 + 2x + -2x Combine like terms: 4x + -2x = 2x 12 + 2x = 30 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 2x = 30 + 0 12 + 2x = 30 Add '-12' to each side of the equation. 12 + -12 + 2x = 30 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 30 + -12 2x = 30 + -12 Combine like terms: 30 + -12 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| w^2-24= | | 8x-6=24 | | -2x^2-4+8x=0 | | 10=x/3+x/7 | | 10=10(y-5)+5y | | -207=1+4(-8v+4) | | 7x-12=3x-16 | | (3a-2b)(3a+3b)=0 | | 6(1-3A)=132 | | 6x-4+2x=28 | | 6(4a+2)=94 | | 6b+10=-14 | | 170-2x=25x+23 | | 3(m+1)+2m=88 | | 2x^2+8y=5x+20 | | 5(8-x)=3x | | -5(6n-4)+2n= | | 3p-3+7p=4p+6 | | 60x=32x | | 60x=26x | | 0.01x+4.74=2.05x-3.42 | | 5*(-2t-3)-(5-(5t+2))=1 | | X^2+8x-xy-8y=0 | | 1/2(4x)=-20 | | 10=15x | | 4x^2-30x+14=0 | | 5x^2-2x=x^2-10x | | 18h*483=462*21h | | 6(3N-1)=-96 | | 3y+5y=64y | | 7y+7=6r+12 | | 12a^5+30a^3-30a=0 |